Decolonizing universalism a transitional feminist ethic - Khader, Serene J. (Studies in feminist philosophy, 2019)
"Develops a genuinely anti-imperialist feminism. Against relativism/universalism debates that ask feminists to either reject normativity or reduce feminism to a Western conceit, Khader's nonideal universalism rediscovers the normative core of feminism in opposition to sexist oppression and reimagines the role of moral ideals in transnational feminist praxis"-- Provided by publisher.